2014
DOI: 10.7150/ijms.8172
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Circulating Advanced Glycation End-Products in Menopausal Women with Osteoporosis

Abstract: Background: Advanced glycation end-products (AGEs) can accumulate in organs and tissues during ageing and diabetes. Increased levels of AGEs are found in the bone tissue of patients with osteoporosis. The purpose of this study was to evaluate circulating AGEs in patients with osteoporosis.Methods: We evaluated plasma AGEs, osteoporosis-related biomarkers, and bone mass in 82 menopausal women with osteoporosis or osteopenia, 16 young women with osteopenia, and 43 healthy women without osteoporosis or osteopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…(54) Although that study did not assess sex-dependent effects, results from another study indicated that AGE accumulation could be correlated to vertebral fracture risk in women but not in men. (55) Taken together, these studies strongly support our finding that AGE accumulation is most detrimental for young female mice, where bone quantity is at lower levels than for males.…”
Section: Discussionsupporting
confidence: 85%
“…(54) Although that study did not assess sex-dependent effects, results from another study indicated that AGE accumulation could be correlated to vertebral fracture risk in women but not in men. (55) Taken together, these studies strongly support our finding that AGE accumulation is most detrimental for young female mice, where bone quantity is at lower levels than for males.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, hyperglycemia is accompanied by an accelerated rate of formation of advanced glycation end-products (AGEs), such as carboxy-methyllysine (CML) and carboxy-ethyllysine (CEL), which are reactive compounds formed by the nonenzymatic reaction between glucose-derived intermediates and free amino groups of proteins. It has been previously demonstrated that the accumulation of AGEs in tissues promotes diabetic nephropathy [ 2 , 3 ], vascular dysfunction [ 4 6 ], diabetic cardiomyopathy [ 7 ], impaired bone formation and increased risk of osteoporosis [ 8 , 9 ], cancer cell proliferation [ 10 ]. Moreover, AGEs accumulation in liver promotes hepatosteatosis and dyslipidemia [ 11 13 ] through the activation of SCAP (sterol-regulatory element binding protein cleavage-activating protein)—SREBP (sterol-regulatory element binding protein) lipogenetic pathway [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ko and his colleagues found that 400 μg/ml AGEs could increase ROS production through suppression of antioxidant Nrf-2 and downstream pathway in H9c2 cells12. Clinically, serum AGEs levels were increased not only in patients with osteoporosis (14.75 vs. 8.12 U/ml)13, but in DM patients with vascular complications (3.40 vs. 1.12 μg/ml)14, indicating that AGEs are associated with cardiac injury resulting from DCM. Both oxidative stress, and inflammation directly triggered by persistent high glucose or AGEs, may occur as upstream events.…”
mentioning
confidence: 98%